Changes in prefrontal cortical activity and turning in response to dopaminergic and cholinergic therapy in Parkinson's disease: A randomized cross-over trial. (May 2021) - Vitorio, Rodrigo; Stuart, Samuel; Giritharan, Andrew; Quinn, Joseph; Nutt, John G.; Mancini, Martina
Abstract: Introduction: Cholinergic dysfunction contributes to mobility deficits in Parkinson's disease (PD). People with PD rely on limited prefrontal executive-attentional resources for the control of locomotion, including turning. Cortical and behavioral responses to cholinergic augmentation during turning remains unclear. We examined prefrontal cortex (PFC) activity while turning-in-place and spatiotemporal measures of turns in response to usual dopaminergic medication and adjunct cholinergic augmentation. Methods: This study consisted of a single-site, randomized, double-blind crossover trial. Twenty PD participants were assessed in the levodopa-off state and then randomized to either levodopa + donepezil (5 mg) or levodopa + placebo treatments for two weeks followed by a 2-week washout before crossover. The primary outcome was change from off state in PFC activity while turning-in-place (assessed with functional near-infrared spectroscopy). Secondary outcomes were changes in spatiotemporal turning measures (assessed with body-worn inertial measurement units) and accuracy in the secondary task. Results: Nineteen participants completed the trial. While levodopa + placebo had no effect on PFC activity when turning-in-place with a dual-task, levodopa + donepezil led to a large reduction in PFC activity (effect size, −0.82). Spatiotemporal measures of turning improved with both treatments, with slightly greater effect sizes observed for levodopa + donepezil. Additionally, the accuracy in the concurrent cognitive task improved only with levodopa + donepezil (effect size, 0.63). Conclusion: The addition of cholinergic therapy with donepezil (5 mg/day for 2 weeks) to standard dopaminergic therapy reduced the burden on prefrontal executive-attentional resources while turning with a dual-task and improved secondary task accuracy and turning. Highlights: A single-site, randomized, double-blinded cross-over clinical trial is presented. Donepezil was administered (5 mg/day for 2 weeks) as adjunct therapy (with levodopa). Nineteen subjects with moderate Parkinson's disease completed the trial. Cholinergic augmentation reduced PFC activity while turning and improved DT accuracy. Turning improved with both treatments (placebo and Donepezil).